Carbon material-loading manganese dioxide nanowire array composite and method for producing same - LI XINLU; HUANG JIAMU; ZHANG YUXIN; JIANG HUAN; SONG HONGFANG; LI HONGYI; XU MIN; WANG HAO; ZHANG YONGLAI; ZHANG JING (2012)
The invention provides a carbon material-loading manganese dioxide nanowire array composite and a method for producing the same, and relates to a manganese dioxide nanocomposite and a method for producing the same. According to the invention, the material consists of a carbon material and manganese dioxide; and the method comprises the steps that the carbon material, potassium permanganate and sulfuric acid are taken as raw materials, and after simple technologies of mixing, stirring, oxidation-reduction reaction, solid-liquid separation, washing and drying, the product is obtained. The method is simple, is convenient to operate, is environment-friendly, consumes less energy, and is low in production cost and convenient to popularize and apply; and the product which is produced through the method has the characteristics of high conductivity, high specific surface area, high proton diffusion coefficient, quick charging and discharging capability, excellent electrochemical performance and the like. The method c